Strengthening Business Sustainability: One-Tier Boards System For Micro-Small Business Enterprises Resailnce After The Enacment Of Law Number 06 Of 2023 About Cipta Kerja - Afriansyah Tanjung (Jurnal Adijaya Multidisplin, 2023)
the obstacle faced by Micro-Small Business Enterprises called as MMBE having strong engagement with business bureaucracy or business organization was barriers the business expansion, credit facilities, and mutual-business cooperation. the existence of PT Perorangan/ PT MMBE was an effective solution to respond and to stimulate the development of PT itself. easy to doing business are indicated from build-up business organization (PT Peorangan) only himself as a founder of legal entity (personal statement) and the model of business-organization management is used one-tier board system (director and commissioner are one board). Mixed-legal research methodologies are selected for this research, secondary data are compulsory (online-library research) while primary data is complementary (field research, used non-probability to determine the population, and purposive sampling is selected for respondents). the data analyzed used the statute approach (primary legal material) and conceptual approach (secondary legal material), the conclusion of this research used the inductive technique and all of the results have been described descriptively. Indonesian government used an economic approach to law for determining the regulation of a one-tier board system in the business-organization management in PT Perorangan/PT MMBE as a media and stimulus for MMBE resilience purposing in Indonesia. one-tier board system is in-line with the PT Perorangan/PT MMBE, it has a correlation to good corporate governance principles that were already regulated in Article 153 Law Number 6 of 2023 on Cipta Kerja